INFLEKSI DAN DERIVASI PADA LIRIK LAGU DALAM ALBUM MANUSIA KARYA TULUS - Nur Aliyatun Mardha Salam; Dakia N. Djou; Salam (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The morphological process of inflection and derivation is related to word formation. The process of word formation in language can be reflected in song lyrics. Songs are one of the most universal forms of human cultural expression. Therefore, this study aims to describe the forms of inflection and derivation and to describe the functions of inflection and derivation in song lyrics in the album Manusia by Tulus. This research, which is classified as qualitative descriptive, has research data in the form of song lyrics containing affixed words. The source of research data comes from ten songs in the album Manusia by Tulus. Data collection techniques were carried out in two ways, namely the free conversational listening technique and the note-taking technique. The research data were analyzed using the distribution method with the direct element sharing technique (BUL). The results of the study showed that the forms of inflection and derivation found in the song lyrics in the album Manusia by Tulus amounted to 15 affixes or affixes consisting of prefixes, infixes, suffixes, and confixes. Then in the inflectional form, nine affixes were found and in the derivation form, 14 affixes were found, each of which has a function. In this derivational form, there are 51 words that experience affixation, while in the inflectional form there are 33 words. So in the song lyrics in the album Manusia by Tulus, derivational affixes are more productive than inflectional affixes.